Impact of surgery in patients with metastatic soft tissue sarcoma: A monocentric retrospective analysis. Issue 1 (28th June 2018) - Wigge, Simone; Heißner, Klaus; Steger, Volker; Ladurner, Ruth; Traub, Frank; Sipos, Bence; Bösmüller, Hans; Kanz, Lothar; Mayer, Frank; Kopp, Hans‐Georg
Abstract : Background and Objectives: The role of local surgical procedures in patients with metastatic soft tissue sarcoma is still undefined. Few retrospective studies have reported survival benefits for patients with pulmonary metastases after complete surgical resection. Treatment decisions are therefore mainly based on personal experiences rather than on reproducible knowledge. Method: A total of 237 patients with metastatic sarcoma, treated between 1982 and 2015 at the University Hospital Tuebingen, Germany, were eligible for inclusion. Out of the 237 screened patients, 102 patients underwent at least one metastasectomy. Overall survival was defined as the primary endpoint in this study. For association of non‐linear relationship to the endpoint, significant prognostic factors were included into a recursive partitioning model. A subgroup analysis for long‐term survivors was also performed. Results: The median overall survival was 64 months. The 3‐, 5‐, 10‐, and 20‐years overall survival rates were 70.7%, 50.3%, 24.7%, and 14.8%, respectively. The number of resections and the progression‐free intervals were independent prognostic factors in three statistical models. Conclusion: Repeated resections of metastases from different localizations are a strong predictor for prolonged survival. We suggest that the progression‐free interval after metastasectomy should be considered as a predictive factor for benefit from further surgery.